2019
DOI: 10.2174/1574888x13666180821160421
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine Mechanisms Involved in Mesenchymal Stem Cell Differentiation into Cardiomyocytes

Abstract: Cardiovascular disease (CVD) is one of a world-wide healthcare problem that involves the heart or blood vessels. CVD includes myocardial infarction and coronary artery diseases (CAD). Dysfunctional myocardial cells are leading causes of low cardiac output or ventricular dysfunction after cardiac arrest and may contribute to the progression of CVD which could not to generate new cardiomyocytes in human adult heart. The mesenchymal stem cells (MSCs) which are present in adult marrow can self-renew and have the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…Accordingly, when compared with d-HuM, d-HuSk also contained growth factors that are commonly stored in the native cardiac matrix, like HGF, IGF, SCF, PDGF, and VEGF, and was enriched with growth factors like bFGF, EGF, GM-CSF, and TGF-beta (Figure 5). These factors are involved in a variety of cardiac processes like cardiac development (Saetrum Opgaard and Wang, 2005;Deshwar et al, 2016), mobilization and proliferation of endothelial progenitor cells (Qiu et al, 2014), angiogenesis and neovascularization (Murakami and Simons, 2008;Beohar et al, 2010), cardiomyocyte proliferation and differentiation (Ma et al, 2017;Farzaneh et al, 2019), cardioprotection (Zhu et al, 2017), cardiac remodeling (Sala and Crepaldi, 2011), and repair (Vandervelde et al, 2005). Such abundance of growth factors in d-HuSk strengthens its suitability for CTE as a promising tool capable of providing alone two of the three pillars of tissue engineering (O'Brien, 2011), namely the scaffold and the signals, and whose potential to boost cardiac regeneration as stand-alone or cellularized scaffold is worth being further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, when compared with d-HuM, d-HuSk also contained growth factors that are commonly stored in the native cardiac matrix, like HGF, IGF, SCF, PDGF, and VEGF, and was enriched with growth factors like bFGF, EGF, GM-CSF, and TGF-beta (Figure 5). These factors are involved in a variety of cardiac processes like cardiac development (Saetrum Opgaard and Wang, 2005;Deshwar et al, 2016), mobilization and proliferation of endothelial progenitor cells (Qiu et al, 2014), angiogenesis and neovascularization (Murakami and Simons, 2008;Beohar et al, 2010), cardiomyocyte proliferation and differentiation (Ma et al, 2017;Farzaneh et al, 2019), cardioprotection (Zhu et al, 2017), cardiac remodeling (Sala and Crepaldi, 2011), and repair (Vandervelde et al, 2005). Such abundance of growth factors in d-HuSk strengthens its suitability for CTE as a promising tool capable of providing alone two of the three pillars of tissue engineering (O'Brien, 2011), namely the scaffold and the signals, and whose potential to boost cardiac regeneration as stand-alone or cellularized scaffold is worth being further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cells of mesodermal origin (osteoblasts, chondroblasts, and adipocytes), MSCs are capable of generating neural cells, hepatocytes, alveolar epithelial cells, insulinproducing cells, cardiomyocytes, indicating their clinical application (7)(8)(9)(10)(11)(12)(13)(14). Several lines of evidence suggested that MSCs have capacity to differentiate into functional cardiomyocytes (9), hepatocytes (10,11), alveolar epithelial cells and lung precursor cells (13) contributing to the regeneration of injured myocardium, liver and lungs (12,(15)(16)(17). Additionally, in paracrine manner, through the production of immunomodulatory factors (indoleamine 2,3-dioxygenase (IDO), prostaglandin E2 (PGE2), nitric oxide (NO), transforming growth factor beta (TGF-β), interleukin (IL)-10, interleukin 1 receptor antagonist (IL-1Ra) and growth related oncogene (GRO), MSCs are able to suppress detrimental autoimmune response and to attenuate autoimmune and chronic, inflammatory diseases (3,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…One limitation of the IGF-1 pretreatment is that it is not clear whether this GF can promote differentiation of MSCs into cardiomyocytes [ 59 ]. On the other hand, HGF is a known regulator of MSCs differentiation into cardiomyocytes [ 60 ]. Therefore, Zhang and colleagues attempted to complement the IGF-1 preconditioning of stem cells with HGF pretreatment [ 59 ].…”
Section: Stem Cell Preconditioning For MI Treatmentmentioning
confidence: 99%